Organizations and complex adaptive systems - Fidanboy, Mahsa (Routledge focus on business and management., 2022)
Organizations and Complex Adaptive Systems explains complexity theory within the organizational studies and discusses theapplicability of complex adaptive systems principles for intraorganizational and interorganizational levels. Complex adaptive systems and complexity theory have been studied in many different fields of science. When studying the application of complex adaptive systems within social sciences, not many are seen in real terms in contrary to the myriads of theories and propositions available. The complex adaptive systems perspective is presented in quantitative terms in natural sciences, but a quantitative approach has not been used within social sciences a lot comparatively. This book links the basics of complex adaptive systems to social sciences, focusing on organizational studies and covering interorganizational, organizational, and individual levels. It shows the latest state of knowledge on the topic and will be of interest to researchers, academics, managers, and students in the fields of management, organizational theory and behavior, and strategic management.- Resumé vydavatel